The influence of threonine:lysine ratios on growth performance and on plasma urea nitrogen in growing-finishing pigs fed from 85 to 240 lb - K G Friesen; L J Kats; K Q Owen; B T Richert; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1993)
Eighty crossbred pigs (initially 85.2 lb BW) were used in a 2 × 4 factorial arrangement to determine the influence of dietary threonine:lysine ratios on growth performance and plasma urea N in growing-finishing pigs. The experiment was conducted in three phases from 85.2 to 124.2, 139.1 to 203.1, and 204.9 to 241.1 lb, with pigs fed one of eight dietary treatments. Two levels of dietary lysine were fed (low vs high) and four levels of dietary threonine were fed within each lysine treatment (60, 65, 70, and 75% of dietary lysine). Dietary lysine decreased from 1.0% and .8% at 85.2 to 124.2 lb to .9 and .7% at 139.1 to 203.1, then to .7 and .5% at 204.9 to 241 1 lb. Average daily gain (ADG) and feed efficiency (F/G) were not influenced by lysine or threonine treatment from 85.2 to 124.2 lb. However, average daily feed intake was decreased for pigs fed 1.0% dietary lysine compared to .8% dietary lysine. From 139.1 to 203.1 lb, an interaction between dietary lysine and threonine existed for ADG. Average daily gain was maximized at 65 and 70% of dietary lysine for pigs fed .7 and .9% dietary lysine, respectively. Conversely, ADFI and F/G were not influenced by threonine:lysine ratios. From 204.9 to 241.1 lb, ADG and ADFI were not influenced by dietary treatment. However, F/G was improved for pigs fed .7% dietary lysine compared to pigs fed .5% dietary lysine. Plasma urea N was increased at 124.2 and at 203.1 for pigs fed greater dietary lysine. At 241.1 lb, plasma urea N was decreased linearly at the percentage of threonine increased from 60 to 75% of lysine. The data from this experiment indicate that excess lysine and threonine intakes do not decrease growth performance. Because high ADFI resulted in high amino acid intake, growth performance was not influenced by the amino acid ratios used in this experiment.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Pigs; Lysine; Threonine; Growth performance